2019
DOI: 10.11152/mu-2164
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal ultrasound investigation (grey scale, Doppler and 2D-SWE) of salivary and lacrimal glands in healthy people and patients with diabetes mellitus and/or obesity, with or without sialosis

Abstract: Aim: To evaluate the ultrasound (US) modifications [grey scale, Doppler, 2D-share wave elastography (2D-SWE)] ofsalivary (parotid and submandibular) and lacrimal glands in healthy people and patients with diabetes mellitus and/or obesity, with or without sialosis.Material and methods: We evaluated 170 patients (1020 glands, 1700 grey scale and Doppler images), split in two groups (group 1- healthy people, group 2- obese and/or diabetes patients, with or without sialosis). For each patient we assessed the parot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In terms of parenchymal elasticity, PG also presented lower values than SMG, assessed with 2D-SWE (5.39±1.45 kPa vs. 8.53±1.89 kPa) [12]. In our group of subjects, gender was not a confounding factor for PG and SMG viscosity and did not influence the elasticity modulus of the major salivary glands assessed with 2D-SWE on healthy subjects [13].…”
Section: Discussionmentioning
confidence: 44%
“…In terms of parenchymal elasticity, PG also presented lower values than SMG, assessed with 2D-SWE (5.39±1.45 kPa vs. 8.53±1.89 kPa) [12]. In our group of subjects, gender was not a confounding factor for PG and SMG viscosity and did not influence the elasticity modulus of the major salivary glands assessed with 2D-SWE on healthy subjects [13].…”
Section: Discussionmentioning
confidence: 44%
“…It may be that GDM causes hyperglycemia in fetuses. As a result, hypertonic diuretic hormone secretion is strong, and fetal urination increases, which leads to polyhydramnios [20][21][22]. Under the stimulation of hyperglycemia, the protein synthesis amount increases, and the birth rate of giant babies increases.…”
Section: Discussionmentioning
confidence: 99%
“…using US criteria such as volume, margins, echotexture, echogenicity, etc. Variable appearance can be found in healthy population; Badarinza et al recently published an atlas with 4 scale grades of parotid echogenicity and found that 12% of healthy non-obese people had inhomogeneous parenchyma (30).…”
Section: Gsusmentioning
confidence: 99%
“…Different surgical procedures (e.g., extracapsular dissection and partial, superficial, total, or radical parotidectomy) can be adapted based on the preoperative knowledge to ensure radicality, the preservation of functional structures as facial nerve and to reduce patient's morbidity (25). A multimodal US pathway includes, besides clinical and laboratory data, the use of GSUS, color-Doppler (CD) US (CDUS), US-elastography and contrast-enhanced US (CEUS) (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%